THE INFLUENCE OF SOCIAL STRATEGY AND PUBLIC POLICY OF STATE DEFENCE AWARENESS MANAGEMENT ON ORGANIZATIONAL PERFORMANCE OF THE MINISTRY OF DEFENSE MEDIATED BY STRATEGIC CHANGE MANAGEMENT - Purwaningsih, Endang; Jasfar, Farida; Kusnadi (International Journal of Research -GRANTHAALAYAH, 2022)
State Defence awarenessis is the collective awareness of the Indonesian nation that is needed by the state to defend its sovereignty, territorial integrity, and national safety in the face of every threat. The aim of the research is to analyze influence variable social strategy and public policy in the State Defence Awareness Management of organization performance of the Ministry of Defense mediated by strategic change management. This study uses quantitative approach with study expanatory. Data analysis using Structural Equation Model (SEM) with using Smart PLS 3.0 for analyze connection or influence variable dependent with variable independent. Research results show that by general there is influence direct social strategy and public policy on organizational performance, as well as there is influence direct strategic change management towards organizational performance as well as there is influence non direct social strategy and public policy to organizational performance mediated by strategic change management. Implication theoretical from this study is strategic change management as mediating social strategic and public policy able for increase organizational performance Ministry of Defense in implementation coaching State Defence Awareness Management. While implication strategic from this study is the strategy, policy, and management changes in the State Defence Awareness Management is very influential to performance Ministry of Defense organization, so that need enhancement every dimension to increase trust public as well as faithfulness every source power involved in implementation coaching State Defence Awareness Management.